Fifteen-minute consultation: Childhood burns: inflicted, neglect or accidental. Issue 2 (22nd June 2018) - Mullen, Stephen; Begley, Roisin; Roberts, Zoe; Kemp, Alison Mary
Abstract : Burns are a relatively common injury in children accounting for over 50 000 emergency department attendances each year. An estimated 1 in 10 of these are due to maltreatment. These may present in the form of physical abuse or neglect with a reported ratio of 1:9. A burn associated with maltreatment may be a marker for future abuse or neglect and it is paramount that concerns are identified and addressed at the initial visit. Paediatricians need to be confident to identify safeguarding concerns specific to childhood burns and investigate accordingly. In this review, key variables that may aid in differentiating maltreatment from accidental burns are discussed in a case-based format, utilising up-to-date evidence to support the recommendations. Despite a proportion of burns resulting from physical abuse, the rate of child protection investigations in these patients are significantly lower than for children who present with other forms of physical injuries despite a similar proportion of positive findings. Our objective is to review the available evidence to support the safe assessment and management of children presenting with scalds or contact burns.